Afetividade e o processos de ensino-aprendizagem: estima de lugar de professores, da Escola de Saúde Pública do Ceará Paulo Marcelo Martins Rodrigues (ESP/CE) - Farias, Nazka Fernandes (2024)
The teaching-learning process, during the COVID-19 Pandemic, went through several tools, transformations and challenges, requiring adaptations, with regard to pedagogical skills, teacher-student relationship and, also, the design of the learning environment, whose the territory(ies) of action have transformed, under different realities. The role of the teacher, in this context, reflected on issues that permeate the field of vulnerability experienced by them in relation to the environment in which they work, during this historical period. The category of affectivity, in this sense, contributes as an important element to the analysis of the teaching-learning process, since emotions, feelings and attitudes affect the way people perceive, interpret and respond to environmental stimuli. Based on studies by Bomfim (2010) and inspired by the Socio-Historical perspective, the concept of Place Estimation, as a socio-environmental category, which can be established as a potentializer or depotentiator, contributes to understanding the person-environment relationship, being, therefore, a path relevant to highlight aspects related to affectivity. In this sense, this Dissertation aims to analyze the Place Estimate of teachers, linked to ESP/CE, who worked in a pandemic context, considering their different functions and aspects related to their teaching practices, as well as focusing on the consequences of the impacts generated by the pandemic, in order to produce data to understand the vulnerabilities that exist in this field, in the light of socio-environmental psychology, which are still incipient. To this end, based on the qualitative approach, with an exploratory study, the following procedures were carried out: I) Semi-structured individual interview to capture aspects about the teaching experience and the implications of the pandemic context and; II) Application of the Affective Map Generator Instrument (IGMA), whose interpretation was anchored in Content Analysis (Bardin, 1977). 15 (fifteen) Affective Maps were produced, which resulted in the prevalence of an Empowering Place Estimate, highlighting the affective image of Empowering Contrast. The result of the participants' Place Estimation Index (IEL) corroborated the affective images produced, as well as the statements highlighted during the interviews carried out, highlighting the importance of the affective representation of the place and its relationship with the teaching-learning process, thus strengthening the perception of actors and practices in a context of social and environmental vulnerability.